Effect of pH on whitening efficacy of 35% hydrogen peroxide and enamel microhardness - Jurema, Ana Luiza Barbosa [UNESP]; de Souza, Mauricio Yugo [UNESP]; Torres, Carlos Rocha Gomes [UNESP]; Borges, Alessandra Bühler [UNESP]; Caneppele, Taciana Marco Ferraz [UNESP] (Wiley, 2018)
Objective: This study aimed to evaluate the effect of 35% hydrogen peroxide at different pH values and the degree of tooth staining on whitening efficacy and enamel microhardness. Materials and Methods: 90 enamel-dentin specimens were obtained from bovine incisors. They were randomly divided into 2 groups (n = 45), 1 group was immersed in a staining broth for 14 days, and another group was not stained and kept in distilled water at 37°C. Twenty-four hours after the staining procedure, each group was distributed into 3 subgroups that were whitened by 35% hydrogen peroxide with different pH values (5, 7, and 8.4) for 30 minutes. The color was measured at baseline and 7 days after whitening. Microhardness was measured at baseline, immediate, 24 hours, and 1 month after the whitening procedure. Data were submitted to 2-way analysis of variance (ANOVA) and the Tukey test for multiple comparisons for color analysis. Repeated measures ANOVA and the Tukey test were used to analyze microhardness data. Results: The color change of the stained groups (ΔE00 = 4.6) was significantly higher than that of the nonstained groups (ΔE00 = 3.7). Microhardness value decreased significantly immediately after whitening for all subgroups and did not return to initial values. For each measurement time, microhardness was not significantly different among subgroups with different pH values. Conclusions: Despite the effectiveness of 35% hydrogen peroxide, changes on gel pH did not affect the whitening efficacy, and the enamel was superficially demineralized, regardless of pH values. Clinical Significance: Independently of the pH value of whitening gel, enamel undergoes superficial demineralization and with a reduction in superficial microhardness that does not return to the initial values. However, using hydrogen peroxide with different pH values does not alter the whitening effect.
Keywords: color change; hydrogen peroxide; whitening